1989
DOI: 10.1002/ajpa.1330790304
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the facial soft tissues

Abstract: Short-base stereophotogrammetry was used to study differential growth and development of the soft tissues of the face. Thirteen facial parameters were measured at ages 9, 11, 13, 15, and 16 years on 170 facial contour maps selected from a mixed longitudinal study of 26 boys and 26 girls. Each parameter was measured three-dimensionally, and its developmental progress at the earlier stages was expressed as a percentage of its value at 16 years of age. Standing height development was assessed in the same way. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Cranial bones grow at a similar rate to that of neural tissue, while bones of the midface follow a "facial" growth pattern, which is midway between the "neural" growth rate and the general skeletal ("somatic") growth rate (Baume et al, 1983;Buschang et al, 1983a). It was found that soft-tissue growth follows the underlying skeleton, e.g., with soft tissues around the orbits showing a "neural" rate of growth, while soft tissues around the maxilla and mandible follow a "facial" rate of growth (Burke and Hughes-Lawson, 1989). Differences between males and females in growth rates of craniofacial bones have been established, with males having greater relative growth than females (Buschang et al, 1983b).…”
Section: Discussionmentioning
confidence: 99%
“…Cranial bones grow at a similar rate to that of neural tissue, while bones of the midface follow a "facial" growth pattern, which is midway between the "neural" growth rate and the general skeletal ("somatic") growth rate (Baume et al, 1983;Buschang et al, 1983a). It was found that soft-tissue growth follows the underlying skeleton, e.g., with soft tissues around the orbits showing a "neural" rate of growth, while soft tissues around the maxilla and mandible follow a "facial" rate of growth (Burke and Hughes-Lawson, 1989). Differences between males and females in growth rates of craniofacial bones have been established, with males having greater relative growth than females (Buschang et al, 1983b).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes in facial proportions, tissue thickness, and facial appearance occur as individuals grow and throughout senescence (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Several studies of facial soft-tissue depth (FSTD) have focused on children with different ethnic backgrounds and skeletal classes including: Caucasian (29)(30)(31)(32), African-American (29,33), Japanese (34,35), Hispanic (29), Class I, II, and III occlusion patterns (30,34,36), and a meta-analysis of pooled FSTD data (37).…”
mentioning
confidence: 99%